Activation of LH GABAergic inputs counteracts fasting‐induced changes in tVTA/RMTG neurons. (13th April 2022) - Godfrey, Nathan; Qiao, Min; Borgland, Stephanie L.
Abstract : Abstract: Dopamine neurons in the ventral tegmental area (VTA) are strongly innervated by GABAergic neurons in the 'tail of the VTA' (tVTA), also known as the rostralmedial tegmental nucleus (RMTg). Disinhibition of dopamine neurons through firing of the GABAergic neurons projecting from the lateral hypothalamus (LH) leads to reward seeking and consumption through dopamine release in the nucleus accumbens. VTA dopamine neurons respond to changes in motivational state, yet less is known about whether tVTA/RMTg GABAergic neurons or the LH GABAergic neurons that project to them are also affected by changes in motivational state, such as fasting. An acute 16 h overnight fast decreased the excitability of tVTA/RMTg GABAergic neurons of male and female mice. In addition, fasting decreased synaptic strength at LH GABA to tVTA/RMTg GABAergic synapses, indicated by reduced amplitude of optically evoked currents, decreased readily releasable pool (RRP) size and replenishment. Optical stimulation of LH GABA terminals suppressed evoked action potentials of tVTA/RMTg GABAergic neurons in unfasted mice, but this effect decreased following fasting. Furthermore, during fasting, LH GABA inputs to tVTA/RMTg neurons maintained functional connectivity during depolarization, as depolarization block was reduced following fasting. Taken together, inhibitory synaptic transmission from LH GABA inputs onto tVTA/RMTg GABAergic neurons decreases following fasting; however, ability to functionally inhibit tVTA/RMTg GABAergic neurons is preserved, allowing for possible disinhibition of dopamine neurons and subsequent foraging. Key points: While dopamine neuronal activity changes with motivational state, it is unknown if fasting influences tVTA/RMTg GABAergic neurons, a major inhibitory input to ventral tegmental area (VTA) dopamine neurons. In unfasted mice, there were sex differences in inhibitory synaptic transmission onto tVTA/RMTg GABAergic neurons. Activation of lateral hypothalamus (LH) GABAergic neurons decreases firing of tVTA/RMTg GABAergic neurons through a monosynaptic input. An acute fast decreases the excitability of tVTA/RMTg GABAergic neurons. An acute fast decreases inhibitory synaptic transmission of the LH GABA input to tVTA/RMTg GABAergic neurons in both male and female mice. Abstract : Abstract figure legend   The inhibitory synaptic input is represented by the downward arrows. Following fasting, there was a decrease in inhibitory synaptic strength in both males and females. The action potentials represent the excitability, which also decreases in both males and females following fasting. Because both the LH GABA input and excitability of tVTA/RMTg GABA neurons have reduced activity following fasting, we predict that disinhibition of dopamine neurons with stimulation of LH inputs is preserved.